Political Law Mining Mineral and Coal When Law Number 23 of 2014 Concerning Regional Government is in Effect - Tamulina Br. Sembiring; Ismaidar Ismaidar; August Saut Maringan Sihombing (Green Social: International Journal of Law and Civil Affairs, 2025)
Enforcement of Law Number 23 of 2014 concerning Government Area change significantly the governance of the energy and mineral resources (ESDM) sector, including mineral and coal mining (minerba). With this regulation, the authority to manage minerba mining is transferred from the district/city government to the central and provincial governments, thus giving rise to various legal implications. Disharmony between Law Number 23 of 2014 and Law Number 4 of 2009 concerning Mineral and Coal Mining shows inconsistencies in the division of authority. This study examines the legal politics which underlies the management of mineral and coal mining in Indonesia, the impact of regulations on regional institutions, as well as importance harmonization regulation to prevent overlapping policies. This study also highlights the importance of implementing the principle of lex specialis derogat legi generali to resolve conflicts of legal norms. The findings indicate the need for revision of related legal products to improve the efficiency and effectiveness of natural resource governance in order to achieve the goal of equitable public welfare.